Agroecology and the limits to resilience: extending the adaptation capacity of agroecosystems to drought - Altieri, Miguel A.; Nicholls, Clara I.; Montalba, Rene; Vieli, Lorena; Vazquez, Luis L. (Frontiers in Agronomy, 2025)
Given the unpredictability, increasing frequency and severity of climatic events, it is crucial to determine the adaptation limits of agroecological strategies adopted by farmers in a range of environments. In times of drought many smallholders’ farmers cope with stress using a series of crop diversification and soil management strategies. Intercropping and agroforestry systems complemented with mulching and copious organic matter applications can increase water storage, enhancing crops’ water use efficiency. Although an overwhelming number of studies demonstrate that these agroecological designs and practices are associated with greater farm-level resilience, it is important to recognize the limits of resilience. The aim of this paper is to assess the limitations of agroecological practices in enhancing the ability of agroecosystems to adapt to climate change under extended drought stress which may overwhelm crops’ adaptation response. A set of agroecological practices that can extend such limits under prolonged water stress scenarios are described. Two methodologies to assess farms’ resilience to drought provide useful tools, as they can assist farmers and researchers in identifying the practices and underlying mechanisms that reduce vulnerability and enhance response capacity allowing certain farm systems to better resist and/or recover from droughts. Clearly, reducing farmers exposure to drought requires collective actions beyond the farm scale (i.e. restoring local watersheds to optimize local hydrological cycles) aspects not explored herein. When climatic events are compounded by uncertainties imposed by external economic and political conditions, farmers’ abilities to overcome adversity may be reduced, emphasizing the importance of policy support, a dimension beyond the scope of this review.